Community Education Through Training on Making Compost from Organic Waste - Fhatya Mulyana Marta (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Creating a sustainable and healthy environment is nevertheless hampered by the community's problems with organic waste disposal. Increasing community members' knowledge, understanding, and creativity in converting organic waste into compost fertilizer is the aim of this compost fertilizer training program. The activity was conducted in Jorong Taratak Indah, Nagari Sungayang, Sungayang Sub-district, Tanah Datar Regency on July 10, 2025, involving 25 participants and 14 KKN students. The methods used included outreach and socialization, starting with a communal dawn prayer, followed by a dawn sermon, then a presentation of theoretical material, and a two-hour practical session on compost making. The training results showed high enthusiasm from the participants, with numerous questions asked and a desire to practice at their respective homes. The activity also produced a sack of compost as an example of the product that can be produced. This training proved effective in providing practical knowledge to the community about managing organic waste into economically valuable products.